1997
DOI: 10.1080/10790268.1997.11719481
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Characteristics of Glutamatergic and GABAergic Terminals in Cat Lamina IX Before and After Spinal Cord Injury

Abstract: The present study was designed to: 1) morpholog ically characterize cat glutamate and GABAergic synaptic term inals in lamina IX in the intact spinal cord at the electron microscopic leve l using postembedding immunochemical techniques and 2), begin an analysis of how the synaptic architecture of glutamate and GABAergic termi nals changes after an ipsilateral spinal cord hemisection. The present study shows that glutamate immunoreactive terminals are characte rized by a wide synaptic cleft, asymmetric synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…This suggestion is supported by the observation that during the acute post-injury phase (i.e., 2 days post-C2Hx; before extensive neuroplasticity and/or anatomical remodeling), PhMNs have already adopted a primarily Late-I phenotype (El-Bohy and Goshgarian, 1999). Progressive increases in PhMN excitability over weeks-months post-C2Hx, as suggested by prior work (Goshgarian, 2009; Tai et al, 1997a; Tai et al, 1997b) may offset the reduction in excitatory bulbospinal inputs to these cells, but without ever fully correcting the C2Hx-induced reductions in phrenic output.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This suggestion is supported by the observation that during the acute post-injury phase (i.e., 2 days post-C2Hx; before extensive neuroplasticity and/or anatomical remodeling), PhMNs have already adopted a primarily Late-I phenotype (El-Bohy and Goshgarian, 1999). Progressive increases in PhMN excitability over weeks-months post-C2Hx, as suggested by prior work (Goshgarian, 2009; Tai et al, 1997a; Tai et al, 1997b) may offset the reduction in excitatory bulbospinal inputs to these cells, but without ever fully correcting the C2Hx-induced reductions in phrenic output.…”
Section: Discussionmentioning
confidence: 76%
“…While definitive testing of this possibility will require intracellular recordings (e.g., (Enriquez Denton et al , 2012)), we hypothesize that decreased PhMN excitability does not explain the observed bursting patterns. Mantilla and colleagues suggested in a preliminary report that PhMN soma size decreases after C2Hx (Mantilla and Sieck, 2009), and molecular changes in and around PhMNs after C2Hx are also consistent with increased excitability (Goshgarian, 2009; Sperry and Goshgarian, 1993; Tai et al, 1997a; Tai et al, 1997b). In our opinion, the more likely scenario is that the decreased burst frequency and Late-I phenotype occur due to the dramatic reduction in bulbospinal synaptic inputs to ipsilateral PhMNs after C2Hx.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In mammalian systems, there is evidence that spinal injury triggers plastic effects in the spinal cord (Edgerton et al 2001;Dietz 2003). This includes changes in the number, size and distribution of synapses (Tai et al 1997), in the properties of neurotransmitter systems (Edgerton et al 2001), and in cellular and synaptic properties (Hochman and McRea 1994;Tillakaratne et al 2002;Li et al 2004). These changes may reflect adaptive plasticity mechanisms (see above) that attempt to compensate for the effects of injury.…”
Section: Spinal Injurymentioning
confidence: 99%
“…The functional recovery in mice is not due to the regeneration of descending inputs, as it persists after the spinal cord is relesioned [57]. The recovery of locomotor function after spinal lesions is associated with changes in synapse structure, including the number, size, and distribution of synapses [58,59], as well as functional changes in cellular and synaptic properties [3,4,52,60].…”
Section: Drug Effects After Spinal Lesionsmentioning
confidence: 98%